Art Therapy through Doodle Art Media in Increasing Learning Concentration Children with ADHD - Bagus Mahardika; Andi Andi Purnawan Putra (Journal of Childhood Development, 2023)
The importance of guiding students in increasing their concentration in learning is the task of an educator. Learning can be digested well when students have adequate concentration and absorption in paying attention to the teacher when explaining the material in front of the class. However, this is certainly different from children with disabilities who require a special approach to be able to receive learning material well. This research aims to see the effectiveness of art therapy using doodle art as a medium, which is expected to improve the concentration of children with ADHD. The research method uses qualitative with a case study approach, to see how the implementation of art therapy improves children's learning concentration. The results of the research show that art therapy with doodle art is able to increase concentration in children with ADHD in the memory aspect, attitude aspect and skill aspect. This approach is chosen according to the conditions and needs of the child, freeing the child to express himself in the doodle art media. It is very effective to see the attitude and enthusiasm of the students during the learning process, they really enjoy it and can relate well to the experiences gained during the learning activities.